Use of theory of games at sports - Perič, Tomáš; Kavalířová, Gabriela (Acta Universitatis Carolinae. Kinanthropologica, 2008)
In practical use we know and quite widely use mathematical methods that lead to process of optimization. In a special group of such methods we recognize schemes, which are used in those cases when different opponents with antagonistic interests compete with one another. On the example of shooting in ice hockey we have demonstrated a use of theory of games. The antagonistic situation exists between shooter (which has two main possibilities - to shoot right above the ice or to the upper part of the goal) and goalkeeper (not to set off or set off against the shot puck and stand or kneel). We have created special pay-off matrices with „cost“ of different strategic possibilities to be able to find the optimal strategic - in our sample - matrix saddle point. These optimal strategies are following - main activity of goalkeeper is setting off against shot pucks and kneeling, on the other hand the shooter should shoot the puck to upper part of the goal. The example also showed the part of the mathematical model that seems to be extraordinary useful at sports.
Keywords: experimentální hry; financování organizované; teorie her; hokej; Statistics as Topic; Game Theory; Humans; Financing, Organized; lidé; teoretické modely; Hockey; Models, Theoretical; statistika jako téma; Sports; sporty; Games, Experimental